Multifunctional emitters for efficient simplified non-doped blueish green organic light emitting devices with extremely low efficiency roll-off. Issue 26 (19th June 2017) - Islam, Amjad; Zhang, Dongdong; Ouyang, Xinhua; Yang, Rongjuan; Lei, Tao; Hong, Ling; Peng, Ruixiang; Duan, Lian; Ge, Ziyi
Abstract : Highly efficient organic light-emitting diodes (OLEDs) with simplified device structures are widely desired for both scientific research and industrial applications. Abstract : Highly efficient organic light-emitting diodes (OLEDs) with simplified device structures are widely desired for both scientific research and industrial applications. However, a very limited number of simplified OLEDs have been reported to date. In this work, two multifunctional blueish green emitters, BPTPETPAI and 2TPETPAI, are designed and synthesized. Owing to the presence of a tetraphenylethene (TPE) moiety, their aggregation induced emission (AIE) properties are also investigated. High photoluminescence efficiencies of the two compounds in non-doped films render them good emitters for non-doped devices. Multilayer non-doped devices based on these emitters achieve maximum external quantum efficiencies (EQEs) and current efficiencies (CEs) of 3.13% and 6.14 cd A −1 as well as 3.25% and 6.70 cd A −1 for BPTPETPAI and 2TPETPAI, respectively. Given their shallow highest occupied molecular orbital (HOMO) energy levels, both emitters can also be used as hole injection and hole transporting materials. Based on this, single layer devices show even higher efficiencies with extremely low efficiency roll-off, achieving maximum CEs as high as 7.12 cd A −1 and 7.80 cd A −1 using BPTPETPAI and 2TPETPAI, respectively. These results demonstrate a bright prospect for the development of highly desired multifunctional emitters as well as simplified OLEDs with significant reduction in the fabrication cost of the device.